Search engine optimization techniques for Malaysian university websites a comparative analysis on Google and Bing search engine - Shahzad, Asim; Mohd Nawi, Nazri; Sutoyo, Edi; Naeem, Muhammad; Ullah, Arif; Naqeeb, Sundas; Aamir, Muhammad (International Journal on Advanced Science, Engineering and Information Technology, 2018)
Search Engine Optimization (SEO) plays a very vital role in the development of professional websites. There are some search engines available on the internet such as Yahoo, Ask.com, AOL.com, Baidu, and Bing. Among which Google is the most widely used search engine. Each search engine uses different SEO technique and algorithm, which not only forms the foundation of SEO but affects the position of a website in organic search results as well. As Google modify its algorithm about 500 or more times per year, the web design and internet also evolves dynamically because of changes in SEO techniques and algorithms. However, how well Malaysian universities websites are optimized for other search engines is questionable particularly the critical differences between search engine ranking techniques and algorithms. This research paper tends to answer these vital questions by proposing a comparative analysis of Bing and Google on some Malaysian universities website, analyzing their search engine optimization parameters and outcomes of using Microsoft Bing as compared to its primary competitor, Google.